Article Commentary: Indicators to Measure Success of Smoke-free Policies - Amanda Niskar (SAGE Publishing, 2008)
The health consequences of involuntary exposure to tobacco smoke are well documented. The past decade provides several examples of successful smoke-free policies that are directly related to improving public health. The objective of this communication is to identify indicators that demonstrate the success of smoke-free policies. Indicators are identified from smoke-free policy evaluations conducted by countries such as the United States, New Zealand, and Israel. Indicators were identified that demonstrate the success of smoke-free policies in the areas of compliance, indoor air quality, bio-monitoring, medical tests, and health behaviors. As smoke-free policies continue to be implemented, indicator evaluation activities should be considered from the start.